ANALISA PUTUSAN PENGADILAN TERKAIT PENGHAPUSAN MEREK YANG TIDAK DIGUNAKAN MENURUT UNDANG-UNDANG NOMOR 15 TAHUN 2001 TENTANG MEREK - Centaury, Patricia Irinne Alpha (JURNAL MEDIA HUKUM DAN PERADILAN, 2018)
Based on the provisions of Article 61 paragraph (2) letter (a) of Law No. 15 of 2001 explains that the brand can be removed from the list of the brands if the brand is not used for three (3) consecutive years from the date of the last registration. One of the problems arise when the brand "IKEA" a famous Sweden brand was successfully removed from the General Registration Brands by a local company. On this research, legal system which are used as a comparison regarding the removal of the brand are the Law Number 15 2001, Sweden Trade Mark Act and the Singapore Trade Mark Act.